TINJAUAN YURIDIS TERHADAP EKSTRADISI ADRIAN KIKI ARIAWAN DALAM KASUS BANTUAN LIKUIDASI BANK INDONESIA - Rahmana, Berty Diah; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Corruption is a threat to the international community . With advanced semakain corruption crime , organized and transnational many perpetrators of corruption who fled abroad . To combat the necessary cooperation among countries in the form of extradition . With the extradition treaty will facilitate the implementation of the investigation , prosecution and punishment for the perpetrators of criminal acts . Based on the above statement is the first purpose of this study , to investigate the implementation of the extradition treaty between Indonesia and Australia , Second , To Know Adrian Kiki Ariawan extradition process that takes a long time and length . From the research, there are twomain issues that can be inferred . First , Extradition treaty between Indonesia and Australia ratified the Law No. 8 of 1994 on the Ratification of the Extradition between Indonesia and Australia . Extradition is required in order to satisfy the justice of society , inorder to uphold the image and authority of the law that core justice and truth . Second, the process of extradition of Adrian Kiki Ariawan basically both Indonesia and Australia have done an extradition treaty in accordance with the rules of each country . Indonesia has formally requested extradition of Adrian Kiki Ariawan and Australia has responded well.Especially Indonesia as the requesting state must follow the procedures or rules that already exist in Australia . Extradition proceedings in Australia against the person who requested the opportunity to make an appeal . Keywords: Corruption-Treaty-Extradition